Diagnostic Enigma in a rare Case of Primary Neuritic Leprosy - Ahmed, Sharif; Rahman, Aminur; Ahmed, Tofael; Hossain, Md Alamgir; Mishu, Mahbubul Hakim; Agarwalla, Ajay Kumar; Russel, Abul Hasnat Md; Khan , Shahjada Mohammad Dastegir; Paul, Biplab; Saha, Pallab Kanti; Islam, Md Daharul (Bangladesh Journal of Medicine, 2024)
Leprosy is one of the most prevalent diseases affecting peripheral nerves. Pure neuritic leprosy accounts for 4-10% of all leprosy cases, with clinical symptoms restricted to the peripheral nerves and no skin abnormalities. Leprosy is diagnosed based on the skin and nerves' typical clinical and histological involvement.The absence of typical dermatological characteristics significantly reduces clinical diagnosis accuracy, necessitating histological confirmation. We presented the case of a 26-year-old male with an 8-year history of growing numbness in his right leg, recurrent ulcers in his right foot, and hand abnormalities. The patient was subsequently identified with pure neural leprosy (PNL), a kind of leprosy that affects peripheral nerves but lacks conventional skin lesions. As a result, in leprosy-endemic countries such as Bangladesh, this kind of leprosy should be extensively explored, especially in patients with no skin abnormalities. Bangladesh J Medicine 2024; 35: 214-217